The complete mitochondrial genome of small wax moth, Achroia grisella (Pyralidae: Galleriinae) - Yangyang Liu; Guoyong Li; Jiankun Long (Mitochondrial DNA. Part B. Resources, 2022)
We sequenced and annotated the complete mitochondrial genome of Achroia grisella (Fabricius, 1794), which was 15,368 bp, encoding 13 protein-coding genes (PCGs), 22 tRNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a control region; having a base composition of A (38.7%), C (12.3%), G (7.5%), T (41.5%), G + C (19.8%), and A + T (71.2%); except for the ND1, which was initiated by the GAT codon, the other 12 PCGs were initiated by the ATN (ATT, ATA, and ATG) codon. The nine PCGs terminated with the typical TAA stop codon, whereas the remaining four genes had incomplete stop codons, which were single T. In addition, the phylogenetic relationships based on nucleotide sequences of 13 PCGs using Bayesian inference (BI) and maximum likelihood (ML) methods showed a close relationship between Achroia grisella and Galleria mellonella.